Wild Profusion : Biodiversity Conservation in an Indonesian Archipelago - Lowe, Celia, 1961- (Book collections on Project MUSE., 2006)
'Wild Profusion' tracks the convergence of Indonesian biologists, Sama people, and flora and fauna in the Togean Islands od Sulawesi to tell the story of biodiversity conservation in 1990s Indonesia.